Chemical Quality Attributes of Refrigerated Mudskipper (Pseudapocryptes elongatus) under Vaccum and Modified Atmosphere Packaging - Minh Phuoc Nguyen (Journal of Global Pharma Technology, 2020)
Modified atmosphere and vacuum packaging were believed as emerging innovative technologies for food preservation. They changed food environment by withdrawing O2 or replacing the atmosphere inside the package by a mixture of gases. Mudskipper (Pseudapocryptes elongatus) has huge potential for coastal aquaculture development and is an alternative to shrimp farming in the Mekong Delta. Mudskipper fishes were refrigerated and stored at 4oC for 21 days under vacuum and modified atmosphere packaging. These samples were analyzed the changes of major chemical parameters such as total volatile base (TVB-N, mg TVB/g), trimethylamine (TMA, mg TMA/g), thiobarbituric acid-reactive substances (TBARS, mg malondialdehyde/kg) during preservation. Results revealed that vacuum packaging could maintain chemical quality attributes for 15 days; meanwhile modified atmosphere packaging could extend the chemical quality indicators for 20 days. It’s obviously presumed that modified atmosphere packaging should be an alternative technology for seafood storage. Keywords: Mudskipper, Vacuum, Modified atmosphere packaging, Total volatile base, Trimethylamine, thiobarbituric acid-reactive substances.